The Role of Islamic Boarding School in The Formation of The Madani Community - Sheema Haseena Armina (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2020)
This study aims to review the concept of civil society as masyarakat madani by looking at the role of pesantren in building civil society in Indonesia. The method is used by descriptive qualitative with library research. The findings of this paper are civil society is an expected society in Islam. The role of Pesantren is representing the diversity of ethnic and various regions of santri consulate in the Islamic environment. The contribution to the development of an Islamic economy with their economic independence either business units or the uniqueness of each Pesantren in Indonesia with the addition that pesantren is the basis genuine for an islamic education learning center in Indonesia.